Impact of bank competition on the interest rate pass-through in the euro area - Michiel van Leuvensteijn; Christoffer Kok Sørensen; Jacob A. Bikker; Adrian A.R.J.M. van Rixtel (European Central Bank (ECB), 2008)
This paper analyses the impact of loan market competition on the interest rates applied by euro area banks to loans and deposits during the 1994-2004 period, using a novel measure of competition called the Boone indicator. We find evidence that stronger competition implies significantly lower spreads between bank and market interest rates for most loan market products. Using an error correction model (ECM) approach to measure the effect of competition on the pass-through of market rates to bank interest rates, we likewise find that banks tend to price their loans more in accordance with the market in countries where competitive pressures are stronger. Further, where loan market competition is stronger, we observe larger bank spreads (implying lower bank interest rates) on current account and time deposits. This would suggest that the competitive pressure is heavier in the loan market than in the deposit markets, so that banks compensate for their reduction in loan market income by lowering their deposit rates. We observe also that bank interest rates in more competitive markets respond more strongly to changes in market interest rates. These findings have important monetary policy implications, as they suggest that measures to enhance competition in the European banking sector will tend to render the monetary policy transmission mechanism more effective.
Keywords: C23; D4; E50; G21; L10; 330; banks; competition; monetary transmission; panel data; retail rates; Geldpolitische Transmission; Zinsstruktur; Kreditgeschäft; Wettbewerb; Privatkundengeschäft; EU-Staaten